TACTICAL OPERATIONS USED IN INVESTIGATING OF FINANCIAL FRAUD - Ivaniuk, Viktoria; Vyshnevskyi, Sviatoslav (Актуальні проблеми правознавства, 2017)
Ivaniuk І., Vyshnevskyi S. Tactical operations used in investigating of fnancial fraud. Abstract. The problems of researching the legal nature of financial fraud are examined. The necessity of adapting national terminology in the domain of financial fraud investigation with the European one, where there is a wider interpretation of the category «fraud» is substantiated. The author analyzes basic typical tactical operations that are used in the investigation of financial fraud.